Maternal Emotional Reminiscing, Child Autobiographical Memory, and Their Associations with Pre-Schoolers' Socioemotional Functioning. Issue 2 (15th March 2022) - Wu, Yun; He, Zijing; Jobson, Laura
ABSTRACT: This study aimed to explore the possible indirect pathway between maternal reminiscing style and child socioemotional functioning (prosocial behaviors and emotional adjustment difficulties) through children's autobiographical memory (elaboration and specificity). A secondary exploratory aim was to examine whether cultural context moderated these indirect effects. Participants included 94 mother-child dyads drawn from middle- and high-income families in China and Australia. The dyads completed measures of child memory specificity, maternal report of child socioemotional functioning, and a shared emotional reminiscing task that assessed child memory elaboration and maternal sensitive guidance. Path analysis results indicated an indirect effect of maternal supportive reminiscing via child memory elaboration (but not memory specificity) on children's prosocial behaviors, regardless of the cultural group. However, there was no evidence to suggest an indirect pathway between maternal supportive reminiscing and child adjustment difficulties (or prosocial behaviors) through child memory specificity in either cultural context. These findings provide preliminary support to the recent conceptualization of an indirect pathway between maternal sensitive guidance during emotional reminiscing and children's prosocial behaviors through child memory elaboration. However, it is important to note that the cross-sectional design limits the causal inferences that can be drawn from the findings. The implications for memory specificity in child socioemotional functioning were less clear and indicated a need for further research in this area.